A unique Pyrenean varved record provides a detailed reconstruction of Mediterranean vegetation and land-use dynamics over the last three millennia. (15th September 2021) - Rull, Valentí; Vegas-Vilarrúbia, Teresa; Corella, Juan Pablo; Trapote, Mari C.; Montoya, Encarni; Valero-Garcés, Blas
Abstract: The Pyrenean Lake Montcortès sediments hold the longest continuous and absolutely varve-dated record of the Mediterranean region, encompassing the last three millennia, from the Late Bronze Age to the present. The reconstruction of vegetation and landscape dynamics during this time period has advanced gradually, following the progress of absolute dating by varve counting, and has been progressively published and updated in a number of papers dealing with specific time intervals at different temporal resolutions. This paper synthesizes all these studies in a single composite paleoecological sequence constrained by a single age-depth varve model. The final resolution of this reconstruction is bidecadal, on average, but some periods have been resolved at quasidecadal (Middle Ages) and subdecadal (Modern Age to present) resolutions. The study is focused on the timing of anthropization and the further development of vegetation under climatic and anthropogenic drivers until the shaping of present landscapes. An additional advantage of Montcortès is that the local history of the Pallars region, where the lake is located, is well documented and can be easily correlated with the paleoecological record. Contrary to former interpretations of general landscape anthropization of the Pyrenees during the Middle Ages, the Montcortès catchment was irreversibly transformed by anthropic activities at the beginning of the Iron Age (ca. 750-650 BCE). From this point, the catchment underwent successive transformations due to varied human uses (fire, grazing, cereal cultivation, weed/ruderal plant expansions, hemp cultivation/retting), which have been related to the different cultural phases and sociopolitical changes documented in the local historical records. The regional forests, dominated by Pinus and Quercus, experienced four main clearance events (RD) during the Iron Age (RD1; ca. 300 BCE), the Roman Period (RD2; ca. 300 CE), the Middle Ages (RD3; ca. 1000 CE) and the Modern Age (RD4; ca. 1800 CE). The detailed trends of the last two deforestation events and their causes could be studied at a decadal resolution, which significantly improved interpretation quality in ecological terms. The potential effects of climatic changes and the eventual interactions with human activities on catchment vegetation and regional forests throughout the record have also been discussed. The Montcortès record has been compared with other records at local (Pyrenees), regional (Iberian Peninsula) and biome (Mediterranean) scales. Locally and regionally, anthropization times and further ecological trends showed significant heterogeneity according to elevation, biogeographical patterns and cultural trends. The most significant coincidence is an intensification of human pressure, as noted in forest clearing and extensive land use, during several phases of the Middle Ages. At the Mediterranean level, the Montcortès record emerges as a unique sequence for the western sector of this biome that should be complemented with similar archives from the central and eastern Mediterranean. The most promising candidates for such sequences are discussed on the basis of available Mediterranean varved records. Graphical abstract: Image 1 Highlights: The longest, continuous and absolutely varve-dated lake record of the Mediterranean region. High-resolution reconstruction of vegetation/landscape trends during the last 3000 years (Bronze Age-present). Emphasis on the role of climatic and anthropogenic drivers, their feedbacks and synergies. Detailed correlations with local archaeological evidence and historical documentation. A potential paleoecological reference section for the western Mediterranean region.